Breastfeeding moderates childhood obesity risk associated with prenatal exposure to excessive gestational weight gain - Susana L. Matias; Christopher E. Anderson; Maria Koleilat (Wiley, 2023)
Abstract Gaining excessive gestational weight may increase obesity risk in the offspring, while breastfeeding lowers that risk. Using data from the Special Supplemental Nutrition Programme for Women, Infants and Children (WIC) in Southern California, we examined the associations between gestational weight gain (GWG), breastfeeding during infancy and childhood obesity at 2-4 years, and determined whether breastfeeding moderated the association between GWG and childhood obesity. GWG was based on weight measurements collected during the first trimester and within a month before delivery. GWG values were standardized by gestational age (GWG z‐scores), per maternal prepregnancy body mass index (BMI) and categorized into tertiles. Fully breastfeeding duration was determined by WIC infant package data indicating the amount of infant formula received monthly. Children's length (or height) and weight measurements were used to calculate BMI‐for‐age z‐scores and identify obesity (z‐score ≥ 95th percentile). Multivariable linear and modified Poisson regression analyses were conducted. Fully breastfeeding moderated the association between GWG z‐scores tertile and obesity in the offspring. Each additional month of fully breastfeeding was associated with 3%-5% obesity risk reduction for each age group and GWG z‐scores tertile, except at age 4 years for children whose mothers had low GWG z‐scores (tertile 1). Shorter fully breastfeeding duration was associated with greater obesity risk among children of mothers with high GWG z‐scores (tertile 3), but not for those whose mothers had low GWG z‐scores. Longer fully breastfeeding duration may provide greater protection against obesity among children at higher risk due to intrauterine exposure to high gestational weight gain.